Knowledge About Sexual Relationship With The Frequency Of Having Sexual Relationship In Trimester Iii Pregnant Women In Pmb Noferia Raraswati Mojosari-Mojokerto - Indah Triningsih; Anggrawati Wulandari (Journal for Research in Public Health, 2021)
The decreased frequency of sexual intercourse in TM III pregnant women is due to a lack of knowledge about sexual intercourse during pregnancy and pregnant women are afraid of hurting their fetus. The purpose of this study was to analyze the relationship between knowledge about sexual intercourse and the frequency of sexual intercourse in third trimester pregnant women at PMB Noferia Raraswati Mojosari. This study is a study using an observational analytic design with a cross sectional approach. The variables in this study consisted of 2 variables, namely the dependent variable and the independent variable using an ordinal scale. The population in this study were all third trimester pregnant women who visited PMB Noferia Raraswati Mojosari-Mojokerto in April-May 2020 with a sample of 32 third trimester pregnant women. The sampling technique used was simple random sampling and the data collection technique in this study used a questionnaire method. The statistical test in this study used Spearman's correlation with a significant level of α = 0.05. The ethics considered in this study consisted of informed consent, annonimity, confidentiallity. The results showed that there was a relationship between knowledge about sexual intercourse and the frequency of sexual intercourse in third trimester pregnant women at PMB Noferia Raraswati Mojosari-Mojokerto with a P value <α = 0.05 (0.006 <0.05). Knowledge of sexual intercourse affects the frequency of sexual intercourse in third trimester pregnant women at PMB Noferia Raraswati Mojosari-Mojokerto.